Analisis Komparatif Pengaruh Sustainability Reporting Berbasis Website dan Kinerja Keuangan terhadap Nilai Perusahaan Konstituen JII dan IDX ESG Leaders di BEI - Mentari Rizki Sawitri Pilomonu; Muliyani Mahmud; Yustina Hiola; Sesylia Mohune; Dirman Dirman (JSAP: Journal Syariah and Accounting Public, 2026)
ABSTRACT: Sustainability reporting has become a global demand [5], with public companies competing to disclose it for a better corporate image and value [10]. Companies included in the Jakarta Islamic Index (JII) constituents that comply with sharia principles and companies indexed in the IDX ESG Leaders that excel in handling environmental, social, and governance issues should be role models in sustainability reporting. Therefore, this study is directed at analyzing the influence of website-based sustainability reporting and financial performance on the value of JII and IDX ESG Leaders constituent companies. In the context of the Indonesian capital market, company value is an important indicator that reflects management performance and investor perceptions. With increasing attention to environmental, social, and governance (ESG) issues, companies are required to focus not only on profits but also on positive impacts for stakeholders [2]. The method used in this study is a comparative quantitative approach, with a sample of companies listed on the JII and IDX ESG Leaders that publish sustainability reports and financial reports. The data collected includes company value as measured by stock price, financial performance as measured by Return on Assets (ROA), and sustainability reports analyzed using the content analysis method. Data analysis was performed using multiple linear regression and the Chow test to identify differences in influence between the two index groups. The expected results of this study are the identification of a significant influence of sustainability reporting and financial performance on company value, as well as recommendations for companies and investors regarding the importance of digital sustainability reporting. Keywords: sustainability reporting, financial performance, company value, JII, IDX ESG Leaders.